(untitled) (Linguostylistic Studies, 2017)
The article deals with the detailed analysis of the religious intertextemes represented in the prose works by Maria Matios («Apocalypse», «Armageddon’s already happened», «Almost never vice versa», «Mother Maritsa», «Our Lady’s Shoes”). The author argues that few attempts have been made by the scholars to investigate the peculiarities of functioning of the precedent religious phenomena as intertextual elements in the creative works by Maria Matios. The study findings give grounds to conclude that in the above mentioned literary works precedent religious phenomena (names, statements, texts, situations) are widely used in the «canonic» and modified forms. In the headlines and narration these linguistic units function as intertextemes that are actualized with the help of textual allusions, textual applications and quoting; they perform signal-informative, organizational and compositional, tuning functions, as well as the function of emotional saturation and traditional customary identification.